The Use Image of Sequence to Improve Students’ Writing Ability Narrative Text (Quasi-Experimental Research on Class VIII Students of SMPN 3 Metro) - Alfina Puji Astuti; Roza, Ahmad Subhan (Journal of English Development, 2026)
Many students still face difficulties in generating ideas, organizing story sequences, and applying appropriate language features. This problem was also identified among eighth-grade students of SMP Negeri 3 Metro, where students’ writing performance was relatively low due to the use of conventional teaching methods and limited visual learning media. This study aimed to examine the effectiveness of using image sequence media in improving students’ narrative writing ability. The research employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest model. The participants consisted of 28 eighth-grade students. Data were collected through writing tests and documentation, and analyzed using the Shapiro–Wilk normality test and the Paired Sample T-Test. The results revealed that the mean pretest score of 40.07 significantly increased to 79.75 in the posttest, with a significance value of 0.000 (< 0.05). These findings indicate that the use of image sequence media has a significant positive effect on students’ narrative writing ability. The study demonstrates that image sequence media effectively assists students in developing ideas, organizing storylines, and improving the overall quality of their writing. Therefore, it can be concluded that image sequence media is an effective instructional strategy for teaching narrative writing at the junior high school level.